WATER CLEANING BY MECHANICAL AND BIOLOGICAL METHODS (Academicia Globe: Inderscience Research, 2023)
Organic substances in wastewater are oxidized with the help of microorganisms. In this, dissolved, colloidal and undissolved substances in water are oxidized. Together with organic substances, incompletely oxidized inorganic substances, namely hydrogen sulfide, ammonia and nitrites, are also reoxidized. Pollutants in water participate in constructive and energy exchange processes in the tissues of microorganisms. Microorganisms can grow in aerobic and anaerobic conditions.